Design of E-KTM Based On Contactless Smartcard for Access Electro Department Parking Service State Polytechnic of Semarang - Sarono Widodo (JAICT, 2016)
E-KTM is an electronic student identification (card ID) card which function besides to student identity, it can be used to access several services at State Polytechnic of Semarang such as to access parking service. In this research, E-KTM has used contactless smart card technology will be used to access facilities parking at electro department area parking. The gate of parking area will be installed two barrier gate to entrance and exit. To access this parking facility, E-KTM must be attached to RFID reader near the entrance gate, and then the barrier gate could open. The system controlled with microcontroller arduino Mega 2560 and will automatically take and save the data of the card ID in database system, and then the infrared sensor would detected the object and a few minutes the barrier gate closed. The system also works for the exit. While the performance to determine average service time with results 2.927 open time and 2.913 close time 2.95 seconds for entrance gate and 2.792 open time and 2.789 close time for exit gate.Index Terms—E-KTM card ID, Parking service, database system